DO INVESTMENTS AND INDEPENDENCY INFLUENCE FIRM PERFORMANCE IN LIGHT OF PERFORMANCE MANAGEMENT: A STUDY IN KUWAIT - Tariq Tawfeeq Yousif Alabdullah; Zahraa Waleed Zubon (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
There has been inconsistency and contradictory findings regarding the relationship between corporate governance mechanisms and performance. This study aims to introduce new concepts by evaluating the impact of board independence and board ownership (managerial ownership) on business success. The analysis in this study utilizes Structural Equation Modeling (SEM) and Partial Least Squares (PLS). The sample consists of 62 manufacturing companies listed on the Kuwait Stock Exchange in 2022. The findings demonstrate the relationship between return on assets and various indicators of company success, including board independence and managerial ownership. The study has practical implications, urging policymakers in Kuwait to prioritize internal control systems in manufacturing companies to contribute more effectively to the country's financial industry. By shedding light on under-researched areas such as the impact of managerial ownership and board independence on firm performance, this study contributes to the existing literature on corporate governance.